Does Diagnostic Certainty Matter?: Pain-Related Stigma in Adolescents with Juvenile Idiopathic Arthritis. (9th March 2023) - Wakefield, Emily O; Belamkar, Vaishali; Sandoval, Ashley; Puhl, Rebecca M; Edelheit, Barbara; Zempsky, William T; Rodrigues, Hannah A; Litt, Mark D
Abstract: Objectives: Childhood chronic pain conditions are common and vulnerable to stigma. Adolescents with chronic primary pain experience diagnostic uncertainty and describe pain-related stigma experiences across multiple social contexts. Juvenile idiopathic arthritis (JIA) is a childhood autoimmune, inflammatory condition with associated chronic pain, but with well-defined diagnostic criteria. The current study examined pain-related stigma experiences in adolescents with JIA. Methods: Four focus groups of 3–7 adolescents with JIA ( N  =   16), ages 12–17 ( M age   =   15.42, SD  =   1.82), and parents ( N  =   13) were conducted to examine experiences of, and reaction to, pain-related stigma. Patients were recruited from an outpatient pediatric rheumatology clinic. Focus group length ranged from 28 to 99 minutes long. Two coders used directed content analysis resulting in 82.17% inter-rater level of agreement. Results: Adolescents with JIA described pain-related stigma experiences predominantly from school teachers and peers, and less from medical providers (e.g., school nurses), and family members after a diagnosis. The primary categories that emerged were (1) Felt Stigma, (2) Internalized Stigma, (3) Anticipatory Stigma/Concealment, and (4) Contributions to Pain-Related Stigma. A common experience of pain-related stigma was the perception by others that the adolescent was too young to have arthritis. Conclusions: In common with adolescents with unexplained chronic pain, our findings indicate that adolescents with JIA experience pain-related stigma in certain social contexts. Diagnostic certainty may contribute to greater support among medical providers and within families. Future research should investigate the impact of pain-related stigma across childhood pain conditions.